Intelligent industrial Processes : Automatic Control Perspective - Birk, Wolfgang (Luleå tekniska universitet, Signaler och system, 2014)
Intelligent Industrial Processes is an area of excellence in research and innovation at Luleå University of Technology (LTU), which was formed to promote multi-disciplinary research and innovation relating to Process Industrial Automation, also referred to as ProcessIT. LTU has a strong track record of research in close collaboration with process industries, where research results have often found their way into products and services strengthening the industries position on the global market.For this area of excellence a road mapping study with respect to Automatic Control research was conducted and is summarized in this white paper. The study shows that current research activities in Automatic Control are very relevant to Intelligent Industrial Processes, dealing with techniques for process understanding (modeling), design and implementation of control systems, and process monitoring, only to mention some.It is concluded that the design and establishment of an Open Research and Innovation Platform is essential for collaborative and multi-disciplinary research in the area. Such a software platform will enable industry partners to more efficiently work with their industrial processes and that in close collaboration with researchers and engineering businesses. At the same time researchers and innovators will have the opportunity to test and validate their results and innovations on real-life cases, enabling a swift exploitation of results. Some key principles for this software platform are the open source, open data and open innovation principles that need to be captured in the platform.The results of that study suggest initial automatic control research activities and a time line for stepping stones towards a full scale implementation of an Open Research and Innovation Platform by 2030. Godkänd; 2014; 20141119 (wolfgang)